Implementación de equipos de monitoreo y seguridad basado en cámaras ip en el almacén Lindón García representaciones del cantón Tosagua. - Paladines Ormaza, Genner Vinicio (2013)
The main objective of this work was to create a security system based on IP cameras, smoke detectors, motion and alarm, warehouse Tosagua State, Lindon Garcia Representations Store, to identify specific risk situation. The security system consists of a web interface to access the cameras from the Internet, to improve control in the daily activities of store managers and customers. For the execution of it is worked with two computing methods and the method of Free Hardware development for the development and implementation of network equipment for the preparation of the graphical interface was used MIDAS development method, where it was necessary to collect information, identify strategic sectors for the installation of equipment, equipment configuration and GUI development, making the whole testing system security emergency drills resulting in the correct operation of the equipment, finally underwent testing the GUI for user access to IP cameras, getting a sense of security for both customers and store owners and workers Lyndon Garcia.